Analisis Kesalahan Penggunaan Bahasa Indonesia dalam Proses Diskusi Siswa Sekolah Dasar - Nila Felasofia Salsabila; Haryadi Haryadi (Journal of Elementary School (JOES), 2022)
This study aims to describe some of the errors in the use of the Indonesian language that were made to the sixth graders of SD Suka Cita. This research uses a descriptive research type, where the source of the data obtained is from discussion activities during class VI SD Suka Cita students. The instrument used in this study is to use observation sheets and tape recorders. The analysis technique used to analyze the Indonesian language error data is a qualitative data analysis technique. The results of this study indicate that there are errors in the use of Indonesian including phonological, morphological, syntactic, and semantic errors in the discussion process carried out by elementary school students. Suggestions from this study, teachers can use the results of analysis regarding language errors made by students as material for learning reflection. Keywords: Error Analysis of Language Usage, Discussion, Students, Elementary School